Respiratory sound analysis using AI/ machine learning algorithms - Zhang, Jingyi (Nanyang Technological University, 2020)
In recent years, AI and machine learning techniques have been applied extensively in many biomedical and healthcare applications. Cardiopulmonary diseases are prevailing diseases and the leading causes of death in many parts of the world. Respiratory sounds are generated by the air flow going in and out of the airways. A dysfunction in the respiratory or cardiovascular system will generate sounds of different characteristics from that of a normal one. As such, pulmonary auscultation has been an extremely valuable tool in the diagnosis of respiratory and cardiovascular conditions. Recently, automated respiratory sound analysis using AI or machine learning algorithms have received much attention from both the academia and the industry.